Salvage Surgery for Esophageal Cancer: How to Improve Outcomes? - Cohen, Charlotte; Tessier, Williams; Gronnier, Caroline; Renaud, Florence; Pasquer, Arnaud; Théreaux, Jérémie; Gagnière, Johan; Meunier, Bernard; Collet, Denis; Piessen, Guillaume; Mariette, Christophe (Annals of surgical oncology, 2018)
Background Locoregional recurrence rates after definitive chemoradiotherapy (dCRT) for locally advanced esophageal cancer (EC) are high. Salvage surgery (SALV) is considered the best treatment option in case of persistent or recurrent disease for operable patients, but SALV has been associated with increased morbidity and mortality. The aim of this study is to identify factors linked to outcomes after SALV to better select candidates and to optimize perioperative care. Study Design We retrospectively analyzed data from 308 consecutive SALV patients from a large multicenter European cohort. Univariate and multivariate analyses were performed to identify factors associated with in-hospital postoperative morbidity, anastomotic leakage (AL), and overall survival (OS). Results The in-hospital postoperative mortality and morbidity rates were 8.4 and 34.7%, respectively. Squamous cell histology ( p = 0.040) and radiation dose ≥ 55 Gy ( p = 0.047) were independently associated with major morbidity. The AL rate was 12.7%, and cervical anastomosis was independently associated with AL ( p = 0.002). OS at 5 years was 34.0%. Radiation dose ≥ 55 Gy ( p = 0.003), occurrence of postoperative complications ( p = 0.006), ypTNM stage 3 ( p = 0.019), and positive surgical margins ( p < 0.001) were linked to poor prognosis. Conclusions SALV is a valuable option for patients with persistent or recurrent disease after dCRT and offers long-term survival. Factors such as radiation dose and anastomosis location identified here will help to optimize outcomes after SALV, which may be considered a standard treatment in the EC therapeutic armamentarium.